(3OQ GdfGXe dQhGjI MaU ef bQGAI YGUes - (3YKeGf Hf YeQ Hf CHj HcQ GdfGTQj, Yaja GdOjf , J (B848 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO , aEfi deG QCjJ Cgd HdOfG RHjO MeGgG Gddg hSGFQ HdGO GdESdGe jSGQYhf Edi GdNjQGJ s
(3BNQgG (B:s
(3hbQC cahkG HhGh HOd GdgeRI ai GdhUd hGdhba hGddg SHMGfg GYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs